SMOOTHING AND CHANGE POINT DETECTION FOR GAMMA RAY COUNT DATA - Leonte D.; Nott D.J.; Dunsmuir W.T.M. (My University, 2003)
Gamma ray detectors are used to measure the natural radioactivity of rocks. For a number of boreholes drilled at a site the gamma ray detector is lowered into each borehole and counts of gamma ray emissions at different depths are recorded as the instrument is gradually raised to ground level. The profile of gamma counts can be informative about the geology at each location. The raw count data are highly variable, and in this paper we describe the use of adaptive smoothing techniques and change point models in order to identify changes in the geology based on the gamma logs. We formulate all our models for the data in the framework of the class of generalized linear models, and describe computational methods for Bayesian inference and model selection for generalized linear models that improve on existing techniques. Application is made to gamma ray data from the Castelreagh Waste Management Centre which served as a hazardous waste disposal facility for the Sydney region between March 1974 and August 1998. Understanding the geological structure of this site is important for further modelling the transport of pollutants beneath the waste disposal area.
Keywords: BAYESIAN INFERENCE; GENERALIZED LINEAR MODELS; MARKOV CHAIN MONTE CARLO; REVERSIBLE JUMP